KUALITAS PELAYANAN PERIZINAN DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PEKANBARU (Studi Kasus Pelayanan Perizinan Tanda Daftar Perusahaan/TDP) - Sartika, Maya; ", Adianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Pekanbaru City’s Investment and Integrated Services Office is a supporter of the mayor’s task in the field of integrated licensing services and investment which has a goal to create exxellent service by making various efforts to improve the succes of its services. This can be seen from the Pekanbaru City DPMPTSP which always gets various kinds of awards each year. The purpose of this study was to determine the quality of licensing services of the Company Register (TDP) in Pekanbaru City to find out the barriers to licensing service quality in Pekanbaru’s One Stop Investment and Services Office (Case Study of Licensing Services for Company Registration Signs. Theory used in research This is Public Service, Public Service Quality, after the research was found that the Quality Indicators of Licensig Services at Pekanbaru City’s Integrated One-Stop Investment and Services Office (Case Study of Licensing Services for Company Registration) are Service Procedures, time of Settlement, Facilities and Infrastructure, and Competence of Service Provider Officers As for the inhibiting factors of Quality of Licensing Services in Pekanbaru City’s One Stop Investment and Services Office (Case Study of Licensing Services for Company Registration) Cnclusion of Quality of Licensing Services at the Investment and Pelay Services The One Stop Inttegrated City of Pekanbaru (Case Study of Licensing Services for Company Registratoin) is the Pekanbaru City One Stop Investment and Services Office which has been said to be successful and acceptable to the community as service users.  Keywords : Services